De novo acute infection and reactivation of hepatitis B virus in established cirrhosis. Issue 6195 (13th October 1979) - Theodossi, A; Wilkinson, S P; Portmann, B; White, Y; Eddleston, A L; Williams, R; Zuckerman, A J
Abstract : Five patients with cirrhosis proved by biopsy had clinical, biochemical, and serological evidence of an acute hepatitis B infection. In two the illness was fulminant and led to death. Only one patient completely recovered. Serological markers for the hepatitis B virus were absent before the onset of the acute illness in four patients, which suggested that a de novo infection had been acquired as a result of recent transfusions of blood or blood products. The fifth patient, who had Goodpasture's syndrome, had antibody to the core of hepatitis B virus, indicating previous exposure to the virus; his acute hepatitis may have been related to immunosuppressive drug treatment, which may have reactivated a dormant virus infection. Thus an acute type B viral hepatitis due to either a de novo or a reactivated infection may be superimposed on cirrhosis.